Fish sensor network: WSN application for fishermen - Suherman,; Al-Akaidi, Marwan (Frontiers in the Internet of Things, 2024)
The scarcity of marine life caused by shallow waters and pollution has pushed fishermen to venture up to 10 km offshore, where clearer waters offer richer fish resources, but at much higher fuel costs. This situation has caused increased unemployment, so many fishermen have changed professions. This is exacerbated by seasonal variations and resource limitations. This research introduces a fish sensor network (FSN), which is designed to equip floating fish houses (FADs) with network-connected fish sensors. The proposed network allows fishermen to find locations with high fish populations, thereby reducing fuel costs and increasing fishing efficiency. This article presents preliminary findings, identifies potential challenges including natural factors such as wind, waves, currents, corrosion, and radio propagation, as well as man-made obstacles such as traffic density and physical measurements at the research site in Belawan, Indonesia. Additionally, this paper briefly discusses the energy availability that poses further challenges.